SUBMARINE LAVA FLOWS: POSSIBLE MECHANISM OF THICK GLASSY CRUST FORMATION - Korinevsky V.G. (My University, 1999)
Submarine pillow basalt lavas with and without glassy crusts are known to differ in structure. A possible cause of thick glassy crust formation is the presence of large amounts of fluids (water) dissolved in the lava, which had remained in this relatively closed system. The contents of fluids in lavas were estimated using the contents of constitutional water (H2O+) determined by the chemical analyses of rock samples. The minimum contents of dissolved H2O+ in lavas were found to range from 2.3-2.5% (sodic basalts) to 3.3-3.5% (sodic-potassic basaltoids).